Challenges and Opportunities of Indian Traditional Medicine in Global Market - Vembu, Thanigavelan; Muniandy, Rajantheran; Murugan, Pitchiah Kumar; Kandasamy, Silllalee S. (Opción)
Traditional Medicine (TM) has been practiced in several countries for many health ailments and disease prevention. For many millions of people, TM regarded as a main source of health care. In relation with culture and history, each race has their own form of medicine. India has different system of medicines viz., Ayurveda, Siddha, Unani and Sowa Rigpa which comes under umbrella “AYUSH” and accepted by WHO. Indian TM particularly Ayurveda Industry has billion dollars of total value market. Among thousands of Pharmaceutical companies in India, only few manufactures doing more than a million dollars’ business to meet the growing demand for Ayurvedic medicine. Siddha Medicine considered as a heritage of Tamil Culture and having potent formulations does not yet enter into the global market even outside the state of Tamil Nadu, India. These TM comprise herbs, minerals and animal products for the production having high impact in economic value due to the usage of environmental assets. Developed countries are moved into the usage of herbal medicine and relaxing their guidelines in the herbal market. European countries share major market 41% of herbal medicine with 70% practitioners prescribes those medicines. WHO forecast, the global market value of herbal medicines (In directly TM) will be 5 Trillion by 2050 having annual growth of 8%. India has rich source of herbal production and using nearly 2000 species in TM and contributes only 1 billion among 62 billion global market. This article discussed about the challenges involved in the production and marketing Indian TM and the scope of opportunities and demand in global market in reference to the WHO Traditional Medicine Strategy. Key challenges such as standardization of raw materials starting from Good Agriculture Practice and Procurement, Investments, Clinical documentation including Pharmacovigilance, Research and Development process, and Regulations and Policies were reviewed.